Social media usage for civic engagement / Anne Marie Warren - Warren, Anne Marie (2014)
In the field of Information Systems, much is known about social media as an Information Technology artefact and its influence, offering various understandings of online human behaviour, particularly for business, psychology and sociology implications. Frequently, research on social media usage can be classified into internal (e.g. entertainment and satisfaction) and external factors (e.g. connection benefits). While these studies on motivations generated a clear link between internal and external factors for social media usage, they did not relate clearly the motivations to the contributions made in terms of civic engagement behaviour. Although there have been calls for research in understanding social media behaviour, its use for positive outcomes and public involvement in civic efforts, few investigations focused on how individuals use social media for addressing social issues. This research introduced a new insight into how social media is shaping the landscape of civic engagement through Facebook in two modes: civic expressions and civic actions. This research examined online civic engagement with reference to the way activists speak, think, and act online in promoting public engagement to curb social issues and the level of civic efforts by individuals. The study focused on understanding the modes of online civic engagement behaviour in addressing the prevalent social problems; the key impetuses of online civic engagement behaviour; and their impact on satisfaction in life and virtual social skills at work. In the absence of defined metrics, this study developed and validated items to measure online civic engagement behaviour. This new construct sheds further light on how individuals use social media for civic engagement by differentiating similar forms of civic interaction. These aspects were researched using three methods: interviews, web analysis and surveys. First, the content analysis of the interviews in Phase 1 revealed five modes of online civic effort: (1) collection of information, (2) publication of information, (3) dialogue, (4) coordination of action, and (5) lobbying decision makers. Three prevalent social problems were identified from the interviews: (1) crime; (2) disengagement from civic matters and moral values; and (3) quality of education. Similarly, these modes were present in the findings of the web analysis of the activists’ social media sites in Phase 2. This allowed the research to proceed to develop new measures for online civic engagement behaviour in Phase 3. Two modes were discovered: civic expressions and civic actions. The structural equation analysis on the 619 responses suggested that civic expressions intensified citizen’s civic actions on Facebook (Phase 4). Moreover, certain trust (trust propensity, trust in social media, trust in institutions) and benefit factors (group incentives and reputation) were found to have a significant impact on the different civic modes. Further, civic actions had a significant impact on satisfaction in life and virtual social skills, producing happy and socially competent working citizens. Interestingly, only users who engaged in civic actions for addressing social issues were satisfied in life. The results suggested that a higher level of virtual social skills had a positive and significant impact on users’ satisfaction in life.